Postpartum common mental disorders and its associated factors in eastern Ethiopia: a community-based cross-sectional study - Tesfaye, Dejene; Misgana, Tadesse; Gebremichael, Berhe; Alemu, Daniel; Tamiru, Dawit; Weldesenbet, Adisu Birhanu; Tariku, Mandaras; Dheresa, Merga (Frontiers in Global Women's Health, 2025)
IntroductionCommon mental disorders (CMD) cause marked emotional distress and interfere with daily function among postpartum women. In addition, the negative attitude towards mental disorders and their treatments prevents the women from seeking mental healthcare. Very little is known about CMD among women, especially in the postpartum period. This study, therefore, aimed at assessing the prevalence of CMD and its associated factors among women in the postpartum period at Kersa and Haramaya Health and Demographic Surveillance Sites (HDSS) sites, in eastern Ethiopia, between 1 July 2021 and 28 February 2022.MethodsThis study employed a community-based cross-sectional study design using a quantitative method and was conducted in Kersa and Haramaya HDSS among 1,016 postpartum women. A structured questionnaire was used to collect data through face-to-face interviews about the variables related to sociodemographic and economic, clinical, psychosocial, substance use, and obstetric complication characteristics. The CMD was assessed by using the Self-Reporting Questionnaire (SRQ-20). A bivariable and multivariable logistic regression analysis was performed. All the variables with a p-value <0.25 in bivariable logistic regression were taken to multivariable logistic regression. Variables with a p-value < 0.05 in the multivariable regression were declared statistically significant associations. The odds ratio (OR) and 95% confidence intervals (CI) were used to show the strength of the association.ResultThe prevalence of postpartum CMD was 23.84% (95% CI: 21.21–26.47). Among pregnant women who had CMD, only 103 (27.7%) had CMD and persisted to the postpartum period. Poor social support [adjusted OR (aOR): 1.88, 95% CI: 1.28–2.74], wealth index in the first quantile (aOR: 1.59, 95% CI: 1.06–2.39), presence of obstetric complication (aOR: 7.74, 95% CI: 4.38–13.69), and cesarean delivery (aOR: 5.01, 95% CI: 1.14–22.13) were the factors that showed a statistically significant association with postpartum CMD.ConclusionOne in every four study participants had CMD, which was higher than in studies conducted in Ethiopia among postpartum women. Social support, wealth index, obstetric complications, and mode of delivery were the factors with statistically significant associations. Postpartum women may benefit from the early diagnosis and treatment of CMD at the community and the primary healthcare level, and the integration of mental healthcare into maternal health services.